Dali Ancient City Tourism Industry Culture and Tourism Publicity Text Translation Characteristics - Shi, Qingyang (Journal of Theory and Practice of Social Science, 2024)
With the continuous development of tourism in Dali, more and more tourists are attracted to visit Dali, including a large number of overseas tourists. Therefore, in order to help overseas tourists better understand the local folk customs and promote the better development of tourism in Dali, this paper, from the perspective of tourism translation texts in Dali and the German functional theory, compares and analyzes the English Translation Materials of tourism texts in Dali. Based on the principles of English-Chinese translation, this paper summarizes the characteristics of tourism text translation in Dali Ancient City from three aspects: vocabulary, grammar and tense. The theoretical basis of this thesis is that the German functional theory can play a useful role in translation practice, especially in non-literary translation and tourism translation. On the one hand, it provides evidence for functional translation theory. On the other hand, it provides some constructive suggestions for English translation of tourism culture materials in Dali. Thus draw the distance between tourists and the propaganda text, so that tourists can not only enjoy the beautiful scenery, but also feel the charm of Dali culture.